2021
DOI: 10.1155/2021/5790416
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Analysis of the Expression and Prognosis for E2Fs in Human Clear Cell Renal Cell Carcinoma

Abstract: Background. E2F transcription factors is a family of transcription factors, and lots of studies have shown that they play a key role in the occurrence and development of many tumors. However, the association between expression, prognostic value, and immune infiltration in the tumor microenvironment of the eight E2Fs members in ccRCC is still unclear. Methods. We used online databases, such as ONCOMINE, UALCAN, Kaplan–Meier plotter, GEPIA, Metascape, TIMER, and cBioPortal, to analyze the effect of mRNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…For example, expression of transcripts corresponding to MYC and E2F targets were negatively associated with OS in both treatment arms, supporting the association of E2F-driven and MYC-driven gene expression with poor prognosis in patients with RCC. [46][47][48] While the association of the HALLMARK fatty acid metabolism gene set with response to sunitinib is in accordance with previously reported data, 49 the current study shows that enrichment of the same gene set is also associated with prolonged survival with nivolumab plus ipilimumab, supporting the hypothesis that expression of genes involved in fatty acid metabolism is a prognostic biomarker for RCC. 50 This is in contrast to the negative correlation between the HALLMARK fatty acid metabolism gene set and response to nivolumab monotherapy in CheckMate 009, where the majority of patients had received prior therapy with VEGF inhibitors.…”
Section: Discussionsupporting
confidence: 92%
“…For example, expression of transcripts corresponding to MYC and E2F targets were negatively associated with OS in both treatment arms, supporting the association of E2F-driven and MYC-driven gene expression with poor prognosis in patients with RCC. [46][47][48] While the association of the HALLMARK fatty acid metabolism gene set with response to sunitinib is in accordance with previously reported data, 49 the current study shows that enrichment of the same gene set is also associated with prolonged survival with nivolumab plus ipilimumab, supporting the hypothesis that expression of genes involved in fatty acid metabolism is a prognostic biomarker for RCC. 50 This is in contrast to the negative correlation between the HALLMARK fatty acid metabolism gene set and response to nivolumab monotherapy in CheckMate 009, where the majority of patients had received prior therapy with VEGF inhibitors.…”
Section: Discussionsupporting
confidence: 92%
“…E2F1 mRNA expression level is related to pathological parameters and is an independently unfavorable factor for OS in clear cell renal cell carcinoma (51). Although E2F1 is one of the most researched E2Fs family members (52), the exact role of E2F1 in LIHC remains controversial and unsettled. It is reported that E2F1 is upregulated in LICH and promotes the development of LIHC via targeting MYBL2 or through being regulated by SIRT5 (15,53).…”
Section: Discussionmentioning
confidence: 99%
“…The Cancer Genome Atlas (TCGA) database is a publicly available database of tumor gene information, containing high-throughput sequencing and pathological data for 30 different cancers. A large number of cancer gene maps can be systematically analyzed to nd out the similarities and differences in the genomic architecture of each cancer and across multiple types (27,28). cBioportal (www.cbioportal.org) is a comprehensive online open source that provides us with visualized and multidimensional cancer genomic data.…”
Section: Tcga and Cbioportal Analysismentioning
confidence: 99%